Development of improved microstructural traits and mechanical integrity of stabilized stainless steel joints of AISI 321. (April 2018) - Devendranath Ramkumar, K.; Pavan, B.; Chandrasekar, V.
Graphical abstract: Highlights: Pulsed current gas tungsten arc welding of Ti stabilized stainless steel using Nb rich and Nb free fillers. Formation of Skeletal, Vermicular delta ferrite in the fusion zone of ER347 and Laves phase in ERNiCrMo-3 welds. Improved microstructure with minimal segregation in ERNiCrMo-4 welds. Pensive discussion on mechanical integrity of the weldments. Abstract: AISI 321, Ti Stabilized austenitic stainless steel joints obtained by pulsed current gas tungsten arc welding process (PCGTAW) using ER347, ERNiCrMo-3 and ERNiCrMo-4 is addressed. The formation of delta ferrite was observed in the fusion zone of ER347 welds. A slight micro-segregation enriched with Mo content was observed in the fusion zone of ERNiCrMo-4 weldments. Tensile studies demonstrated that the failures occurred in the weld zone for ER347 and ERNiCrMo-3 and in base metal for ERNiCrMo-4 weldments. The formation of deleterious Laves phase in the fusion zone lowered the notch impact toughness and weld tensile properties for ERNiCrMo-3 weldments. The structure-property relationship of AISI 321 welds are addressed in detail and suitable recommendation on the choice of filler material is made based on the research findings.